Haploidentical hematopoietic stem cell transplantation as individual treatment option in pediatric patients with very high-risk sarcomas - Eichholz, Thomas; Döring, Michaela; Giardino, Stefano; Gruhn, Bernd; Seitz, Christian; Flaadt, Tim; Schwinger, Wolfgang; Ebinger, Martin; Holzer, Ursula; Mezger, Markus; Teltschik, Heiko-Manuel; Sparber-Sauer, Monika; et al. (Frontiers in Oncology, 2023)
Background: Prognosis of children with primary disseminated or metastatic relapsed sarcomas remains dismal despite intensification of conventional therapies including high-dose chemotherapy. Since haploidentical hematopoietic stem cell transplantation (haplo-HSCT) is effective in the treatment of hematological malignancies by mediating a graft versus leukemia effect, we evaluated this approach in pediatric sarcomas as well. Methods: Patients with bone Ewing sarcoma or soft tissue sarcoma who received haplo-HSCT as part of clinical trials using CD3+ or TCRα/ß and CD19+ depletion respectively were evaluated regarding feasibility of treatment and survival. Results: We identified 15 patients with primary disseminated disease and 14 with metastatic relapse who were transplanted from a haploidentical donor to improve prognosis. Three-year event-free survival (EFS) was 18,1% and predominantly determined by relapse and death of disease. Survival depended on response to pre-transplant therapy (3y-EFS of patients in complete or very good partial response: 36,4%). However, no patient with metastatic relapse could be rescued. Conclusion: Haplo-HSCT for consolidation after conventional therapy seems not to be sufficient to improve outcome of high-risk pediatric sarcomas. Evaluation of its future use as basis for subsequent humoral or cellular immunotherapies is necessary.